AGRI-ENVIRONMENTAL PRACTICES FOR LAND USE AS A PREREQUISITE FOR BUILDING A SUSTAINABLE AGRI-FOOD SYSTEM - D. Kirechev (Trakia Journal of Sciences)
The study analyses the potential of agroecological practices in agricultural land use to ensure increased sustainability of the agri-food system. Conventional agricultural practices are perceived to have an increasingly negative impact on land use, necessitating the adoption of new approaches. In the context of climate change, the role of sustainable land management and its ability to sequester carbon is increasing. The need to support farmers adopting agri-environmental practices is highlighted. The introduction of such practices is seen as a major factor in improving the supply of healthy and safe food.